STUDY OF LOW ENROLMENT IN M.ED. COURSES BASED ON JAMMU DIVISION IN INDIA - Kalubovitiyana Soratha Thero (Indonesian Journal of Social Science Education (IJSSE), 2026)
Finding the causes of the low enrollment in the M.Ed. program is the aim of this study. To accomplish the goals of the study, the researcher will employ the survey research method. In order to produce capable educational leaders, policymakers, and researchers, the Master of Education (M.Ed.) program is crucial. However, many schools have seen a drop in enrollment in recent years, which is alarming given the growing demand for high-quality education and changes that call for qualified workers. To produce such professionals, high-quality teacher education primarily through programs like the M.Ed. is essential. The results demonstrate that educational planners, legislators, and institutions are gravely concerned about the reasons behind low enrollment. Students’ choices may be influenced by elements including few employment options, expensive tuition, a lack of understanding of the program’s worth, and competition from other courses. By recognizing these problems, institutions can boost postgraduate education and increase enrollment.